Giant nonlinearity in a superconducting sub-terahertz metamaterial - Savinov, V. (2016)
We report a superconducting sub-THz metamaterial operating in a CW-regime, which exhibits a record-breaking resonant third-order nonlinearity with effective n2∼10 cm2/W. The nonlinear response is caused by the radiation-induced resistive heating, suppressing the superconductivity in the nano-scale constrictions of the structure's meta-molecules. The nonlinearity has a relaxation time of 25 μs and leads to a substantial change of the amplitude and phase of the transmitted radiation at intensities of only 500 μW/cm.